The impact of Islamic banking financing formats (Murabaha; Musharaka; Mudaraba and Salam) on inflation in the State of Sudan - a standard study during the period 2010 to 2019 - - ghorab, hanane; boucenna, mehamed ridha (Journal of Research in Finance and Accounting, 2023)
The purpose of this study is to analyze the impact of Islamic banking financing formats (Murabaha, Salam, Mudaraba, Musharaka) on inflation in the State of Sudan, Using monthly data from 2010 to 2019, the study followed the VECM error correction beam, Which measured the impact between Islamic banking and inflation forms, the results of which were a long-term balance between Islamic banking and inflation, but a very small proportion. in which it found a positive long-term and short-term relationship between the formula of participation and inflation, Either the Murabaha formula found that there was only a positive long-term relationship, the rest of the formulas (Salam, Mudaraba) It has been observed that there is only a negative relationship in the long term.